Donor-acceptor interactions : transition metal carbonyl group ligand [TM(CO)6]q complexes. A case study at correlated level from the topological density point of view - Bochicchio, Roberto Carlos (2019)
Fil: Bochicchio, Roberto Carlos. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales, Departamento de Física; Argentina.